Ramona forever - Cleary, Beverly; Tiegreen, Alan (New York : Morrow Junior Books, 1984)
A lot happens during Ramona's year in third grade, highlighted by the arrival of Howie's rich uncle, a change in her after-school situation, a surprise wedding, a death and a new arrival in the family, and her father's getting a job.
Elem. School Library Collection.
School Library Journal.
Horn Book.
5.1
3-6
Keywords: Family life -- Fiction; Quimby, Ramona (Fictitious character) -- Fiction; Family life -- Fiction; Quimby, Ramona (Fictional character) -- Fiction; Family life -- Fiction